Peran Gender Kontemporer di Indonesia - Perubahan dan Keberlanjutan: Studi Pustaka - Nugraha, Sumedi P.; Susilastuti, Dewi Haryani (Universitas Islam Indonesia, 2022)
This study aims to find out the way gender socialization affects the young people’s perception on men and women roles. This paper uses state-supported gender roles in the Soeharto era as a benchmark for gender ideology today. The government of Soeharto marked a pivotal moment in the development of the expected roles of men and women both in the public and private areas. The aims of this paper are: (1) to explore whether gender roles in Indonesia have shifted from the Soeharto era to the present, (2) to examine what messages are conveyed by TV, schools and social media as agents of socialization, and (3) to look at young people's perceptions of